2012
DOI: 10.1152/ajpheart.00063.2012
|View full text |Cite
|
Sign up to set email alerts
|

The role of neuregulin/ErbB2/ErbB4 signaling in the heart with special focus on effects on cardiomyocyte proliferation

Abstract: Wadugu B, Kühn B. The role of neuregulin/ErbB2/ErbB4 signaling in the heart with special focus on effects on cardiomyocyte proliferation. Am J Physiol Heart Circ Physiol 302: H2139 -H2147, 2012. First published March 16, 2012 doi:10.1152/ajpheart.00063.2012.-The signaling complex consisting of the growth factor neuregulin-1 (NRG1) and its tyrosine kinase receptors ErbB2 and ErbB4 has a critical role in cardiac development and homeostasis of the structure and function of the adult heart. Recent research result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
87
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(92 citation statements)
references
References 98 publications
(143 reference statements)
2
87
1
1
Order By: Relevance
“…This pathway normally acts as a response/repair mechanism to a broad range of myocardial injury. 7 Administration of trastuzumab blocks the ErbB2 receptor, leading to potential myocardial injury via disruption of repair mechanisms. Myocardial trastuzumab uptake is particularly common shortly after anthracycline administration, providing mechanistic evidence to support the clinical observation of the high rates of cardiotoxicity when these agents are used in close temporal relationship to one another.…”
Section: Mechanisms Of Cardiotoxicitymentioning
confidence: 99%
“…This pathway normally acts as a response/repair mechanism to a broad range of myocardial injury. 7 Administration of trastuzumab blocks the ErbB2 receptor, leading to potential myocardial injury via disruption of repair mechanisms. Myocardial trastuzumab uptake is particularly common shortly after anthracycline administration, providing mechanistic evidence to support the clinical observation of the high rates of cardiotoxicity when these agents are used in close temporal relationship to one another.…”
Section: Mechanisms Of Cardiotoxicitymentioning
confidence: 99%
“…Among the podcasts we produced on the overarching topic of signaling and stress response (34,63,99), several featured articles emerged as seminal discussions. We brought the complexities and importance of O-linked N-acetylglucosamine signaling into context by exploring the work of Facundo et al (25).…”
Section: Podcastsmentioning
confidence: 99%
“…Using a unique and innovative large animal model, Walker et al (101) focused on the oft-ignored issue of right ventricular cardiac disease. The groundbreaking research by Ma et al (56) provided a platform to discuss new methods for generating large quantities of cultured cardiac myocytes using embryoid body formation and blasticidin selection techniques.Among the podcasts we produced on the overarching topic of signaling and stress response (34,63,99), several featured articles emerged as seminal discussions. We brought the complexities and importance of O-linked N-acetylglucosamine signaling into context by exploring the work of Facundo et al (25).…”
mentioning
confidence: 99%
“…Past studies have shown that cardiomyocyte hyperplastic growth occurs in response to input from a large network of growth factor signaling pathways (Lavine et al, 2005;Ahuja et al, 2007;Bersell et al, 2009;Heallen et al, 2011;Porrello et al, 2011;Xin et al, 2011Xin et al, , 2013Eulalio et al, 2012;von Gise et al, 2012;Wadugu and Kuhn, 2012). However, many basic questions regarding the mechanisms underlying how these growth factors regulate the cardiomyocyte cell cycle remain unanswered.…”
Section: Introductionmentioning
confidence: 99%